EPIZOIC FAUNA ON THE FLATHEAD LOCUST LOBSTER, THENUS ORIENTALIS (LUND) - Lazarus, R J; Reddy, P Sita Rami; Thangavelu, R (Indian Journal of Fisheries, 2011)
The incidence of sessile barnacles (Balanus amphitrite communis) andpedunculate cirripeds {Octolasmis warwickii and O. tridens) on the carapace andof O. cor var. A, O. co/- var. B and O. cor var. C in the branchial chamber ofThenus orientalis are reported